(untitled) (Universal International Scientific Journal, 2026)
Literary texts are an important discourse field that reflects the relationship between language and thought at the conceptual level. This thesis analyzes the cognitive-pragmatic content of the concept of "justice" within this discourse and its place in the conceptosphere. The study interprets the concept of "justice" as a central semantic unit that constitutes the plot and conflict, and identifies its normative, evaluative, punitive and moral components. It also shows that justice is conceptualized through the metaphors of balance, judgment, path and punishment. The results of the analysis confirm that the concept of "justice" is universal in conceptosphere and is manifested in artistic discourses in accordance with cultural characteristics.